INVESTIGASI PENGGUNAAN PROGRAM ILEGAL PADA GAME NARUTO X BORUTO NINJA VOLTAGE MENGGUNAKAN METODE LIVE FORENSICS INVESTIGATION - Muhammad Rizky Gaez; Budi Indiarto; Mardiana Purwaningsih; Mochammad Isnin Faried; Fandan Dwi Nugroho Wicaksono (Institut Teknologi dan Bisnis Swadharma, 2025)
This study aims to investigate the use of illegal programs in the game “Naruto X Boruto Ninja Voltage” due to the increasing use of illegal programs such as cheats and hacks, thus threatening the integrity and balance of the game environment. In addition, this study also identifies behavioral patterns associated with the use of illegal programs. In order to achieve these goals, the Live Forensics Investigation method is applied with a focus on monitoring and analyzing game activity in real time on various devices. The investigation involves observing the interaction between players and the game server and identifying signs that indicate the use of illegal programs. A digital forensics approach is used to collect digital evidence, track suspicious data flows, and understand the techniques perpetrators of illegal programs use. This study experimented with changing the basic variables into Health Point (HP), Chakra Point (CP), Attack, and Defense on the character. The results of the trial of changing the basic variables on the characters Naruto (The Final Showdown) and Sasuke (The Final Showdown), which was carried out at various stages, showed that the characters whose basic variables have been changed can complete the stage easily and are very difficult to die (immortal). The study’s results successfully implemented the live forensics method to determine the types of illegal programs most commonly used in the game “Naruto X Boruto Ninja Voltage” and their impact on the gaming experience. This study also identified typical behavioral patterns associated with illegal programs, such as abnormal activity or suspicious spikes in capabilities. This research is very valuable for game developers and platform organizers. The information obtained from this study can be used to design and implement better protection mechanisms, including early detection of illegal programs, the application of appropriate sanctions against violators, and regular updates to address vulnerabilities in the system.Penelitian ini bertujuan untuk menginvestigasi penggunaan program ilegal dalam permainan